The presence of Cronobacter sakazakii, Enterobacteriaceae spp. and Ochratoxin-A in Infant Rice-based formula and milled rice products - Asya Cetinkaya; Sibel Ozcakmak (Hittite Journal of Science and Engineering, 2018)
R ice based products could be have microbiological and toxicological hazards causing for unsuitable production and storage conditions. In this study, samples of three different commercial Infant Rice-based formulae with four samples IRF , nine milled rice MR samples were searched for Cronobacter sakazakii, Enterobacteriaceae spp. and Ochratoxin-A OTA . The presence of C. sakazakii and Enterobacteriaceae spp. was detected using ISO/TS 22964/IDF/RM 210 and and ISO 21528-2: 2004 method, respectively. A developed method using OCHRAPREP® REFN: A9-P14.V4 in conjunction with HPLC described by AOAC 2000.003 was used with slight modifications of the purification and HPLC conditions and with another confirmation method for OTA. The limit of quantities measurement was 1.286 μg/kg. C. sakazakii was not found in any samples. Enterobacteriaceae spp. was determined above the legal limits between 2.6x102 and 2.8x104 kob/g, average 3.46x104 in four samples 30.77% . OTA was detected by one IRF with milk product sample with 0.60 μg/kg 7.69%